PENDIDIKAN ANTI KORUPSI; UPAYA PREVENTIF MEMBERANTAS KORUPSI - Mohammad Kosim (Karsa: Journal of Social and Islamic Culture)
This writing will describe corruption that up to now still become big problem for a number of countries, especially for the poor and developing ones. The negative effect of corruption is  both from the material side and immaterial. Therefore, with any reasons, corruption cannot be accepted and must be eliminated. The elimination of corruption must be done repressively and preventively. One of the preventive ways proposed in this writing is trough education anti corruption, especially trough family and school.